EFFECT OF FUROSTANOL GLYCOSIDES FROM CULTURED DIOSCOREA DELTOIDEA CELLS ON REGULATORY FUNCTION OF ENDOTHELIUM IN A RAT MODEL OF HYPOESTROGEN-INDUCED ENDOTHELIAL DYSFUNCTION - E. B. Artyushkova; N. G. Gumanova; V. A. Metelskaya; T. G. Pokrovskaya; V. I. Kochkarov; M. V. Korokin; M. V. Pokrovsky; L. V. Korokina; A. M. Nosov; M. M. Korneev (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To study the effects of furostanol glycosides from cultured Dioscorea Deltoidea cells (DM-05, Institute of Plant Physiology, RAS) on physiological and biochemical markers of endothelial function in rats with hypoestrogen-induced endothelial dysfunction.Material and methods. 10 female rats of Wistar line, with body mass 200-300 g have been included in the experiment. The bilateral ovariectomy was performed in rats to produce the model of hypoestrogen-induced endothelial dysfunction. Rats were treated with the injections of DM-05 during 6 weeks. False ovariectomy was performed in rats of control group (n=10).Results. DM-05 restored the levels of stable metabolites of nitric oxide (NO) which reflex endothelial NO-synthase activity. Besides DM-05 corrected blood pressure and endothelial function. Experiments on open heart showed that DM-05 protects the cardiac tissue from hypoestrogen-induced hyperadrenoreactivity.Conclusion. Treatment with plant origin substances with estrogen-like activity can be a perspective approach to the correction of endothelial function and decrease in cardiovascular risk in menopause women.